OPTIMIZING READING COMPREHENSION SKILL WITH THE STUDENTS` TEAM ACHIEVEMENT DIVISION (STAD) METHOD - Tahir, Nur'ain; Talib, Rasuna Rasid; Malabar, Fahria (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This research aims to determine whether the use of the Students’ Team Achievement Division (STAD) method can significantly improve students’ reading comprehension skills. This research focused on five indicators of reading comprehension: vocabulary, main idea, specific information, reference, and inference. The sample of this research was class X Computer and Network Engineering at SMK Negeri 5 Gorontalo, consisting of 25 students. This research used a quantitative method, specifically a pre-experimental design with pre-test, treatment, and post-test. The instrument used was a multiple-choice objective test. The results showed a significant improvement in students’ reading comprehension skills after the implementation of the STAD method. This is evidenced by the difference in scores between the pre-test and post-test and further supported by hypothesis testing, in which Ha is accepted and Ho is rejected. Based on the Paired Sample T-Test, if the Sig. (2-tailed) If the value is less than 0.05, it indicates that the STAD method has a significant effect. In this study, the Sig. (2-tailed) The value was 0.000, which is less than 0.05, thus proving that the STAD method effectively improves students’ reading comprehension skills.